Breathe - Book 1 - Crossan, Sarah (New York : Greenwillow Books, 2012)
"In a barren land, a shimmering glass dome houses the survivors of the Switch, the period when oxygen levels plunged and the green world withered. A state lottery meant a lucky few won safety, while the rest suffocated in the thin air. And now Alina, Quinn, and Bea--an unlikely trio, each with their own agendas, their own longings and fears--walk straight into the heart of danger. With two days worth of oxygen in their tanks, they leave the dome. What will happen on the third day?"--
HL700
Accelerated Reader
Keywords: Science fiction; Survival; Juvenile fiction; Insurgency; Juvenile fiction; Environmental degradation; Juvenile fiction; Survival -- Fiction; Shipwreck survival; Fiction; Adventure stories; Insurgency; Fiction; Environmental degradation; Fiction; Survival -- Fiction; Adventure and adventurers; Fiction